Methods and means of forming verbal messages in ergotic systems - Давлетьянц A. A. (Proceedings of National Aviation University, 2000)
Presented are the methods of forming verbal (oral) messages and their comparative characteristic. Expediency of PC usage as a tool of formation, playback, storage and registration of verbal messages is motivated. As an example, automatic system dealing with preparation and transmission of messages covering the airport terminal is presented. Performance algorithm and description of programming block of signal quality evaluation in broadcasting network are provided